Numerical Study of Water Infiltration in Biochar-amended Landfill Covers under Seasonal Variations - Apriyono, Arwan; Yuliana; Chen, Zhongkui; Kamchoom , Viroon (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 28, 2023)
The utilization of biochar as an environmentally sustainable material has garnered attention in recent years for its ability to enhance soil properties, such as mechanical and hydraulic characteristics. Nevertheless, a comprehensive understanding of the effects of biochar on water infiltration in landfill covers, especially with regards to variations in rainfall and evaporation patterns, is limited. This study aims to investigate the effects of biochar on soil water infiltration extreme climate. To do this research, finite element analyses were conducted using SEEP/W under a two-dimensional axis-symmetry condition. Both drying and wetting SWRC data from the experiment were fitted with the van Genuchten model and implemented into the numerical models. Moreover, A series of numerical analysis was performed to observe the PWP response during extreme rainfall and evaporation events. The results of this study indicate that the addition of biochar to CDG led to a delay in the response time of water infiltration, reducing the depth of the wetting front and slowing down water infiltration. Furthermore, the addition of biochar can significantly reduce the increasing of PWP during infiltration under extreme climate.